A Pilot Study of Confocal Laser Endomicroscopy to Predict Barrier Dysfunction and Relapse in Pediatric Inflammatory Bowel Disease. Issue 6 (June 2016) - Shavrov, Anton; Kharitonova, Anastasia Y.; Davis, Elisabeth M.; Claggett, Brian; Morozov, Dmitriy A.; Brown, Daniel K.; Shavrov, Andrey A.; Liu, Julia J.
ABSTRACT: Objectives: Probe-based confocal laser endomicroscopy (pCLE) is a novel imaging modality that enables virtual optical biopsy in vivo. Loss of barrier function of the small bowel observed via pCLE as increased density of epithelial gaps (extrusion zones left in the intestinal lining after cells are shed) is predictive of relapse in adult patients with inflammatory bowel disease (IBD). This study aims to determine whether such observations on pCLE are similarly predictive of disease relapse in pediatric patients with IBD. Methods: Pediatric patients with biopsy-proven IBD underwent pCLE during colonoscopy and subsequent clinical follow-up every 6 months. Relapse was defined as moderate to severe flare with endoscopic evidence of inflammation during the follow-up period. The relations between epithelial gap density, disease relapse, and imaging parameters were determined using Cox models. Results: Twenty-four patients with IBD (13 with Crohn disease, 11 with ulcerative colitis) with a median age of 14 years (range 10–21) were studied for a median of 13 (4–33) months. The median duration of disease was 2.9 years (range 0–9). Increased epithelial gap density in the terminal ileum on pCLE of normal endoscopic appearing terminal ileum mucosa ( N  = 19) was predictive of disease relapse when 3 or more areas were imaged (N = 6, log-rank P  = 0.02, C-statistic = 0.94). Conclusions: In pediatric patients with IBD, barrier dysfunction observed on pCLE imaging of the small bowel was predictive of disease relapse.